Just give me one more chance to make it right!

Algebra Level 3

If x x is a value that satisfies the equation

( x + 1 ) 2 = 3 x + 2 (x+1)^{2} = 3x +2

,then, which of the following is the value of x 6 x^{6} ?

Note: This question may be lengthy, but the point of this question is its length.

3 x + 1 3x +1 12 x + 8 12x + 8 5 x + 3 5x + 3 8 x + 5 8x + 5

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Ronak Agarwal
Aug 12, 2014

Opening the bracket and rearranging terms we get :

x 2 = x + 1 {x}^{2}=x+1 (i) Multiplying both sides by x we get

x 3 = x 2 + x {x}^{3}={x}^{2}+x Using (i) we get

x 3 = ( x + 1 ) + x = 2 x + 1 {x}^{3}=(x+1)+x=2x+1 Squaring both sides to get

x 6 = 4 x 2 + 4 x + 1 {x}^{6}=4{x}^{2}+4{x}+1 Again using (i) we get

x 6 = 4 ( x + 1 ) + 4 x + 1 = 8 x + 5 \boxed{{x}^{6}=4(x+1)+4x+1=8x+5}

Of course one can generalise the fact(and prove it by induction) that :

x n = F n + 1 x + F n {x}^{n}={F}_{n+1}x+{F}_{n} where F n {F}_{n} is the n t h nth term of fibbonaci series

Ok, the solution of the equation is phi and psi which are involved in the general term for Fibonacci sequence. But Ronak, how did you come up with the x^n thing?

Avinash Pandey - 6 years, 10 months ago

Log in to reply

I said that it can be proved by induction.

Ronak Agarwal - 6 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...